Effect of antisense mitogen-activated protein kinase oligonucleotides on rat vascular smooth muscle cell proliferation induced by EGF in vitro. - Huang Shao-Ling; Ding Bo; Yu Qing-Sheng; Guo Zhao-Gui (Acta Pharmacologica Sinica, 2016)
AIM: To study the preventive effect of down-regulating mitogen-activated protein kinase (MAPK) on vascular smooth muscle cell (VSMC) proliferation. METHODS: Cultured rat VSMC was pretreated with a phosphorothioate-protected 17-mer antisense MAPK oligodeoxynucleotides (ODN) directed against the initiation of translation sites of the p42- and p44-MAPK isoforms by liposomal transfection. A 17-mer sense and a random sequence MAPK ODN were used as control. After liposomal transfection, cells were exposed to epidermal growth factor (EGF) 1 nmol.L-1 for 10 min and then harvested in lysis buffer. MAPK activity was measured by Western blot and P-81 phosphocellulose filter papers method by using [gamma-32P] ATP and myelin basic protein as substrate. DNA synthesis was measured by [3H]thymidine incorporation. RESULTS: Antisense ODN 0.2 mumol.L-1 reduced EGF-induced MAPK activities by 84%, and inhibited VSMC [3H]thymidine incorporation stimulated by EGF. CONCLUSION: A 17-mer MAPK antisense oligonucleotide directed against the initiation of translation sites of the p44- and p42-MAPK inhibited EGF-stimulated rat VSMC proliferation.